Sejarah dan Perkembangan Perguruan Pencak Silat MS Jalan Enam Pengasinan dalam Perspektif Historis dan Sosiokultural - Rahmawati, Citra Ashri; Salam, Fitrah Febri; Suwandi; Berwantoro, Ramdan; Hanafi, Imam (CV. Kurnia Grup, 2024)
The MS Jalan Enam Pengasinan Silat School is one of the martial arts schools that has developed since 1978 and plays an important role in the preservation of traditional Indonesian martial arts. This study aims to analyze the history, development, and contributions of the MS Jalan Enam Pengasinan Silat School in the context of cultural preservation and traditional martial arts. The research uses a qualitative approach with documentary studies and in-depth interviews with the school`s members and administrators. The results of the study indicate that visionary leadership, commitment to tradition, and efforts to adapt to modern developments are the main factors in the succes of this school. Furthermore, the MS Jalan Enam Pengasinan Silat School has succeeded in introducing traditional Indonesian martial arts to the international stage. This school not only plays a role in developing the physical and mental abilities of its members but also contributes to strengthening social cohesion in the community while preserving the values of Indonesian culture.